Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

To repel the red imported fire ant: a review of progress, limitations, and prospects - Chengju Du; Chao Wen; Rui Pang; Cai Wang (Current Opinion in Insect Science, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

DSAP-WeedNet: A Down-Scale Attention-Guided Lightweight Network for Real-Time Weed Detection Enabling Precision Control in Potato Fields - Lei Han; Yi-Teng Wu; Ke-Jun Fan; Rui-Feng Wang; Wen-Hao Su (Potato Research, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Influence of circumferential gap on the axial compressive behaviour of circular CFDST stub columns: Tests, numerical analysis and design method - Pei-Jia Dai; Rui Wang; Hui Zhao; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Experimental and numerical study of diaphragm in-plane stiffness on the seismic performance of building structures with DCPCF - Yuan-yuan Sun; Rui Pang; Shu-ting Liang; Yi-ming Wen; Chun-lin Wang (Engineering Structures, 2026)

Axial compression behavior of circular CFDST stub columns with localized corrosion: Testing, numerical modeling and design - Guangdi You; Hui Zhao; Rui Wang; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Recycled seawater chlorine in the lithospheric mantle facilitates metal enrichment in collisional orogens - Jingbo Zhang; Rui Wang; Zoltán Zajacz; Alexandra Tsay; Adam C. Simon; Wen-Jie Xia; Yun-Zhao Ge; Zeng-Qian Hou (Earth and Planetary Science Letters, 2026)

Planarization engineering of benzodithiophene-based nanogrids for enhanced carrier mobility and emission performance - Lei Yang; Jun Yang; Shi-rui Chen; Wen-bin Xie; Cong Sun; Wang-yang Wu; Xin-zhe Peng; Manas Ranjan Dash; Xue-qin Ran; Mohamad Akbar Ali; Ling-hai Xie (Chemical Engineering Journal, 2026)

Design of a biomimetic walking wheel inspired by reindeer hoof morphology and its snow-terrain locomotion performance - Kaixiang Chen; Rui Zhang; Mingxi Yu; Huailiang Wang; Hao Pang; Lige Wen (Cold Regions Science and Technology, 2026)

Literature-based spatiotemporal patterns of Hyalomma asiaticum and associated pathogen risks along the Belt and Road Economic Corridors - Jingyi Wen; Chaoqun Wu; Wei Wei; Chengyu Ma; Zhengyi Li; Rigai Sa; Guoshuai Li; Yaxian Du; Rui Wang (Veterinary Parasitology, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Using spherical protrusions for simultaneous pressure pulsation mitigation and efficiency enhancement in a giant Francis turbine across a wide load operation - Lei Tang; Xiao-Wen Huang; Rui Zhao; Tian-Yi Shi; Wen-Quan Wang (Ocean Engineering, 2026)

Rapid burial and exhumation of the Kohistan arc root, Western Himalaya - Wen-Rui Sun; Rui Wang; Xin Zhong; Xinyi Zhong (Lithos, 2026)

Diverse subducted sediments and ambient mantle wedge heterogeneity caused spatiotemporal variations in the composition of gabbroic rocks in the Gangdese Batholith, southern Tibet - Rui-Qiang Wang; Jian-Sheng Qiu; Ding-Jun Wen; Timothy Chapman; Ying Xia; Yue Chen (Lithos, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Effect of liquefaction solvent, catalyst sulfidation method and H2S on mild liquefaction behaviors of Jiangna coal over Fe-based catalysts - Jiaqi Yu; Yuxin Wen; Shuo Wang; Rui Zhang; He Yang; Yang Li; Xingxing Xiao; Yining Guan; Haoquan Hu; Lijun Jin (Fuel, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Interfacial engineering enables confined growth of ultrafine CsPbBr3 quantum dots on UiO-66-g-P4VP for efficient photocatalytic CO2 reduction - Xinru Ding; Xinxing Zhang; Rui Ding; Tao Wen; Ziqun Wang; Lei Sun; Wenzhong Yang; Ling Huang; Hui Xu (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Spirofluorene-grafted triazine branched poly(aryl piperidinium) anion exchange membranes for high performance water electrolysis and flow batteries - Wei-Feng Yang; Yong-Xin An; Rui Guo; Han Yan; Tian-Tian Wang; Chang-Ping Liu; Yong-Mei Tian; Wen-Bin Sun (Chemical Engineering Journal, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Seed Germination in Red Mud: Roles of Plant Traits and Metal Availability - Jian-Rui Wang; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo; Rui-Xia Ma; Jing-Jing Feng (Water, Air, & Soil Pollution, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Dissolved inorganic phosphorus enrichment in groundwater of phosphate mining areas driven by multiple biogenic pathways - Junna Ning; Yao Du; Tianming Wu; Mengze Li; Baisong Deng; Wen Zhang; Yiqun Gan; Haomiao Yang; Xiaoxia Chen; Rui Ma; Yanxin Wang (Water Research, 2026)

Decadal Evolution, spatial Heterogeneity, and drivers of China’s highway vehicle emissions - Xiaomeng Wu; Youchao Wang; Yifan Wen; Daoyuan Yang; Rui Wu; Shaojun Zhang; Ye Wu (Transportation Research Part D: Transport and Environment, 2026)

Freeze-thaw damage evolution and crack propagation failure mechanism of red sandstone under non-uniform water distribution conditions - Li Wenbo; Sun Jielong; Chen Rui; Wang Yu; Wen Ziyi; Lou Bing (Transportation Geotechnics, 2026)

Environmentally relevant imidacloprid exposure elicits hippocampal microglial apoptosis via JNK-FOXO3 pathway: Implication for latent central neurotoxicity - Xinyi Wen; Meiyan Li; Zhongyuan Zhang; Jingwen Wang; Hao Hu; Weihong Wang; Jing Jin; Kairong Wang; Jian Sun; Rui Zhang (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

A novel physics-driven remeshing technique for particle finite element method - Wen-Rui Sun; Ke-Jian Wang; Wen-Qi Guan; Xue Li; Wei Zhang; Wei-Hai Yuan (Computers and Geotechnics, 2026)

Modulating the crystal growth of manganese oxide via carbon fiber for efficient water purification with peroxyacetic acid oxidation - Rui Gan; Lijuan Huang; Rongling Wang; Yuxuan Ye; Qiang Li; Wen Liu; Yuwei Deng; Junxiong Cai; Fei Pan (Chemical Engineering Journal, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Composite beeswax-glycerol monolaurate oleogelation enhances encapsulation efficiency and oxidative stability of microencapsulated Antarctic krill oil - Xin Sun; Liang Song; Rui-Ying Wang; Xin-Yang Ha; Fa-Wen Yin; Lei Qin; Bei-Wei Zhu; Da-Yong Zhou (Food Research International, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Increasing carbon emissions despite declining burned area in the Northern Hemisphere wildfires - Rui Shi; Yuhui He; Ruitong Guo; Xiaofan Wang; Yaliang Hou; Yue Zhou; Xiaoying Niu; Hui Wen; Jun Liu; Wei Pu; Xin Wang; Dongyou Wu (Atmospheric Research, 2026)

Prevalence and associated factors of Anaplasma, Rickettsia, and Coxiella-related bacteria in ticks in China: A systematic review and meta-analysis - Pengcheng Bian; Wei Wei; Zhengyi Li; Lu An; Jingyi Wen; Rui Wang (Experimental and Applied Acarology, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Biological Aging Mediates the Associations Between Multiple Serum Micronutrients and All-Cause Mortality Among U.S. Adults - Chaoyi Bian; Wanting Wang; Zhengyang Wu; Hongling Zhang; Chuanting Wen; Kangkang Zhong; Rui Yang; Qi Zhong (Biological Trace Element Research, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Effects of Hofmeister cation series induced by different alkalizers on the production, structural and functional characteristics of low-sodium soy protein fractions - Yu Peng; Rui Wang; Mo Li; Xin Wen; Yuanying Ni; Sirinan Lasrichan (Food Hydrocolloids, 2026)

Engineered MBene-integrated anisotropic aerogel with synergistic hydrogen-bond network and superior photothermal conversion for efficient solar-driven desalination and purification - Xinyi Wang; Rongtao Zheng; Cuilian Wen; Lijin Luo; Jiansen Wen; Haonan Zhao; Rui Xiong; Frank Marken; Yin Yuan; Baisheng Sa (Desalination, 2026)

High-efficiency integration of capacitive deionization and electricity generation in single cycle enabled by basswood-derived free-standing carbon electrode - Yao Qiu; Rui Zhang; Shuyu Kong; Yishuo Teng; Dongling Li; Ming Hou; Jingwen Wang; Yongzhao Hou; Guangwu Wen; Dong Wang (Desalination, 2026)

All-in-one transparent radiative cooler: Integrating daylighting, passive cooling, and triboelectric power generation for energy-saving buildings - Yuxuan Gu; Rui Chen; Yageng Bai; Fengyu Wen; Yashu He; Jierun Ma; Haoyuan Tan; Yifan Wang; Pengbo Lian; Haikun Zhu; Jianxin Mu (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Engineering selective pathways for photocatalytic methyl mercaptan oxidation via spatially separated redox centers in Sr-modified carbon nitride - Shanrong Li; Jiali Wang; Shuangqing Liu; Fanghua Zeng; Zhiqi Wen; Rui Xiong; Can Yang (ENGINEERING Environment, 2026)

Combined Effects and Potential Mechanisms of Multiple Metals Exposure on Coronary Artery Disease in the US Population: An Integrated Epidemiological and Network Toxicology Study - Chaoyi Bian; Chuanting Wen; Kangkang Zhong; Wanting Wang; Rui Yang; Qi Zhong (Biological Trace Element Research, 2026)

Influence of Rate Effects on Fracture-Induced Opening of Interlayer Branch Fractures - Wen-rui Wang; Zong-qing Zhou; Hua-qing Ma; Xue-lin Zheng; Lei Chen; Cheng-lu Gao; Zhi-yuan Liu (Rock Mechanics and Rock Engineering, 2026)

Self-powered electron transfer on single-atom dual-reaction center: Achieving high-efficiency catalysis in oxidant-free systems - Wen Song; Enyu Zhao; Qinyi Wang; Pijun Duan; Xuguang Li; Tao Yan; Yanxia Zhao; Rui Feng; Yunhui Zhang; Yuanyuan Qu; Xing Xu; Liangguo Yan (Water Research, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Epidemiology and associated factors of human and canine leptospirosis in China: a systematic review and meta-analysis - Wei Wei; Di Jiao; Xinyue Dong; Rui Shi; Rigai Sa; Chengyu Ma; Lu An; Jingyi Wen; Xiaoqian Zhang; Rui Wang (Preventive Veterinary Medicine, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Insights to Geometrical and Mechanical Representative Elementary Volume (REV) from a DFN Approach: A Case Study of the Lanping Lead–Zinc Mine - Yan Gu; Rui Yong; Nick Barton; Wen-Jie Xu; Ze Li; Changshuo Wang; Jibo Qin (Rock Mechanics and Rock Engineering, 2026)

Gut microbiota and growth differentiation in koi carp with identification of a growth promoting Exiguobacterium sp. strain WY(Y)3 - Rui-Qi Wang; Ahmed E. Elshafey; Zhuo-Tao Liu; Bin Wen; Jian-Zhong Gao; Zai-Zhong Chen (World Journal of Microbiology and Biotechnology, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Synergistic effects of internal FeB doping and external SiC/C dual coating on micro-Si anode performance - Shuai Wang; Qinyu Wu; Rui Cao; Zhenfei Cai; Xiaolong Ma; Zhongqiu Chu; Zhuo Zhao; Yangzhou Ma; Guangsheng Song; Cuie Wen (Chemical Engineering Journal, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Experimental and numerical investigations on hysteretic behaviour of tapered RAC-filled high-strength double-skin steel tubular columns - Yupeng Guo; Rui Wang; Hui Zhao; Yunhe Wang; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

Laminarin attenuates neuroinflammation in MPTP-induced Parkinson’s disease mouse model via inhibiting dectin-1/Syk/NF-κB signaling - Rui-Yue Zhao; Mei Zhang; Xiao-Wen Wang; Feng Xue; Yang-Yang Zheng; Wen-Fang Chen (Inflammopharmacology, 2026)

Promoting Aquatic Animal Health and Water Quality: A Systematic Review on Probiotics, Prebiotics and Synbiotics in Aquaculture - Yaxin Wen; Miao Wang; Haoran Wang; Shilin Liu; Ronglian Xing; Hongxia Zhang; Lihong Chen; Rui Li; Zhen Yu (Fishes, 2026)
Background: Aquaculture, a vital component of global food security, faces sustainability challenges due to intensive farming practices, including water pollution, disease outbreaks, and antibiotic overuse. Probiotics, prebiotics, and synbiotics have emerged as eco-friendly alternatives to antibiotics. However, research results remain heterogeneous across aquatic species and intervention strategies. Methods: Following PRISMA 2020, we searched two databases (up to January 2026) for in vivo trials. Two reviewers screened and extracted data, and 177 eligible studies were ultimately included, covering single-/multi-strain probiotics (SSP/MSP), live/inactivated microbial preparations, and diverse synbiotic formulations. Results: Among 177 studies, Bacillus spp. were the most widely reported and effective probiotic strains. MSP and synbiotics exhibited superior efficacy in boosting aquatic animal growth performance and disease resistance over SSP in 68% of the included trials. Probiotics act through the competitive exclusion of pathogens, immune modulation, and enhanced digestive enzyme activity; prebiotics selectively stimulate beneficial gut microbiota, improving nutrient absorption and immune function through metabolites such as short-chain fatty acids; synbiotics combine the advantages of both, exerting synergistic effects. Furthermore, as water additives or fermented feed ingredients, probiotics reduce nitrogenous waste and organic pollutants, contributing to bioremediation. Conclusions: All three additives are effective. Standardized application protocols and long-term trials are needed for sustainable aquaculture. This review provides a unified evidence-based foundation for the rational use of these additives in aquaculture.

Reduction of regulatory B cells is associated with high-risk clinical stratification in antiphospholipid syndrome patients - Rui Ma; You-yang Wang; Jing-hong Feng; Wen-yi Li; Yan Long (Immunologic Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Soil type regulates the development and insecticide susceptibility of Spodoptera frugiperda by modulating maize growth and nutritional content - Shi-Wen Deng; Mohammed Esmail Abdalla Elzaki; Wei Liang; Muhammad Hafeez; Wan-Ting Li; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Pulsed electric field facilitated fibrillation of soy protein isolate: preparation, characterization, and functional properties - Dong-Yang Xu; Ben Yu; Wen-Hao Xiao; Zhong Han; Rui Wang; Xin-An Zeng (Food Hydrocolloids, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Multifunctional deep learning-based mechanical-laser collaborative adaptive precision weeding system for lettuce - Rui Hu; Lei Kong; Wen-Hao Su; Bo-Wen Dong; Yujin Wang; Xiaobin Li; Yankun Peng (Computers and Electronics in Agriculture, 2026)

Spatiotemporal trends and risk factors of small-ruminant brucellosis in China: A systematic review and meta-analysis - Wei Wei; Di Jiao; Rui Shi; Rigai Sa; Zhengyi Li; Lu An; Xiaoqian Zhang; Jingyi Wen; Rui Wang (The Veterinary Journal, 2026)

Plant protoberberine alkaloids: structural diversity, biosynthesis, synthesis, biological activity, structure-activity relationships and clinical applications of berberine - Weiqi Jiang; Wen Zhang; Chenxin Jing; Han Zhou; Zhi-Jun Zhang; Rui Wang; Ying-Qian Liu (Phytochemistry, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Highly stretchable and self-adhesive PEDOT:PSS blends via coulombic repulsion-induced weakening of interchain interaction - Xiaoxue Lin; Rui Chen; Zeping Ou; Wen Sun; Lei Wang; Zhihan Zeng; Hanlin Cheng; Kuan Sun; Jianyong Ouyang (Chemical Engineering Journal, 2026)

From gasification slag to high-rate anodes: Synergy of open nanopores and defects for superior sodium-ion kinetics - Jingwen Huang; Haiqiang Bai; Xiaohua Wang; Yujie He; Jing Zhang; Rui Ding; Jinghui Yang; Ling Kang; Junfeng Wen; Lisheng Zhong; Yunhua Xu (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Changes in soil multifunctionality under different grazing intensities in spring are mainly influenced by the stability of soil biota networks - Hansen Gao; Rui Wang; Yali Yin; Wen Zhao; Wenxian Zheng; Xueao Song; Haiqiang Liu; Shixiong Li (Agriculture, Ecosystems & Environment, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Multi-omics analyses identify the modulators COX6A1 and NAL as regulators of silk cocoon formation in Plutella xylostella - Rui-Chang Niu; Qing-Hui Zeng; Wen-Jing Wang; Jia Hu; Tong-Xian Liu; Shi-Ze Zhang (Pesticide Biochemistry and Physiology, 2026)

A novel multi-scale structural equivalent method for jointed rock masses and its application to slope stability analysis - Jia Wang; Wen Zhang; Han Yin; Rui Fu; Qi Sun; Jiali Han; Junqi Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Coexisting wet and damp magma fractionation in the middle crust: An example from the Gangdese Batholith in southern Tibet - Rui-Qiang Wang; Di-Cheng Zhu; Ding-Jun Wen; Ying Xia; Yue Chen (Gondwana Research, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Seawater desalination in China: Current situation, problems, and development prospects - Rui hao Wang; Cheng peng Wang; Sheng hui Wang; Dai wang Song; Pengfei Huang; Xiaoli Wang; Ren wen Ma (Desalination, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Xinshuaining preparation ameliorates doxorubicin-induced cardiac injury in heart failure rats by regulating gut microbiota - Qian Nie; Jue Zhao; Sattar Haseeb; Siwei Deng; Xin Zhang; Rui Wang; Xu Luo; Wen Xie (Drug Delivery and Translational Research, 2026)

Measuring intercontinental-scale geopotential difference using atomic clock frequency comparison with PPP technique - Kuangchao Wu; Wen-Bin Shen; Hok Sum Fok; Zengzeng Lian; Pengfei Zhang; Lihong Li; Lei Wang; An Ning; Rui Xu; Ziyu Shen (Advances in Space Research, 2026)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

900 Wh L–1 lithium-ion batteries enabled by self-assembled copolymer induced built-in electric field on graphite anode - Yumeng Zhao; Changdong Li; Dehua Xu; Rui Li; Bin Han; Xinlian Chen; Bohua Wen; Haimei Xie; Aoxuan Wang; Jiayan Luo (Science Bulletin, 2025)

Clonal budding and a sessile stalk in conulariids suggested by a new genus from China - Hui Min; Rui-Wen Zong; Xun-Lian Wang (Palaeoworld, 2025)

Discriminating nanoparticulate and ionic silver in vivo: Organ-specific distribution and toxicological outcomes via gold-core labeling - Xiang-Rui Wang; Dingyuan Liang; Xiaoli Zhao; Ying Wang; Wen-Hong Fan (Journal of Hazardous Materials, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Real-time rockburst warning using microseismic multi-feature parameters based on the PSO-GRNN model - Wen Xuan Dong; Qing He Zhang; Xiao Rui Wang; He Peng Dong; Chuan Bing Wang; Sheng tao Wang (Natural Hazards, 2025)

SARS-CoV-2 nucleocapsid protein induces a Mincle-dependent macrophage inflammatory response in acute kidney injury - Rui-zhi Tan; Wen-jing Zhao; Jing Gao; Hui-yao Lan; Jian Liu; Li Wang (Inflammation Research, 2025)

Comparative pan-genome analysis of Huperzia and Phlegmariurus and transcriptomics reveals thermal adaptation in Huperzia - Muzi Li; Yazhu Wu; Haibo Li; Zhongnian Zhang; Rui Qin; Jiahao Wen; Yeqin Xu; Chengcheng Bao; Dekai Wang (Functional & Integrative Genomics, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Machine learning-assisted magnetic nanomotors for the identification and degradation of organic pollutants - Zhiqin Geng; Gang Wang; Bohan Gu; Bingxue Wen; Ziwen Wu; Rui Li; Linfen Duan; Yunsheng Shang; Weiqing Han; Kajia Wei; Lulu Qu (Journal of Hazardous Materials, 2025)

A multiscale peridynamic simulation on thermal-mechanical coupling behavior and damage failure mechanism of granite - Heng Li; Sheng-Qi Yang; Rui Yong; Shi-Gui Du; Bo-Wen Sun; Su-Sheng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Advanced strategies in organoid/organ-on-a-chip for food safety and nutrition - Yiyan Zhou; Feiran Wang; Rui Zhao; Tianyi Huang; Wentao Su; Ya Wen; Zhixian He; Dong Li (Food Research International, 2025)

The effect of microplastic pollution on rice growth, paddy soil properties, and greenhouse gas emissions: A global meta-analysis - Shi-Wen Deng; Wei Liang; Hong-Yu Chen; Mutaz Mohammed Abdallah; Rui-Long Wang (Environmental Research, 2025)

Optimizing lithium extraction from brines using fluoride-doped lithium titanate in hybrid capacitive deionization - Jiahui Zhang; Wen Xi; Jianing Hu; Qingqing Han; Youfang Zhang; Shuo Huang; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Desalination, 2025)

Collaborative effects of Sr2+ and copolymer antiscalant / fulvic acid on nanofiltration membrane fouling behavior - Hailong Wang; Yunhuan Chen; Xincheng Wen; Rui Zhang; Xugang Song; Qiang Ma; Xiaoxiao Duan; Yongsheng Ren (Desalination, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

“Phenology description is all you need!” mapping unknown crop types with remote sensing time-series and LLM generated text alignment - Siyuan Wen; Wenzhi Zhao; Fengcheng Ji; Rui Peng; Liqiang Zhang; Qiao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Metal salt modulation strategy to prepare highly defective coal-based porous carbon for solid-state zinc ion hybrid capacitors - Pengxu Ren; Haolan Wen; Tao Wang; Yafen Zheng; Rui Sheng; Dongling Wu (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Orally administered milk-derived extracellular vesicles alleviate hepatic metabolic dysfunction by targeting hepatocytes and modulating ER stress - Rui Zhang; Haoran Wang; Guoyue Wei; Xipeng Sun; Yifan Zou; Chaoting Wen; Tao Li; Huaxi Yi; Lingjun Tong (Chemical Engineering Journal, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Interactions and feedback mechanisms in oasis wetland hydrology–soil–vegetation systems, northwestern China - Bing Liu; Ying Zhao; Arash Malekian; Xiao Wang; Wenzhi Zhao; Maliheh Behrang Manesh; Bin Wang; Changkun Yang; Weihao Sun; Wen Li; Pouyan Dehghan Rahimabadi; Yangyang Meng; et al. (CATENA, 2025)

Evaluating the Role of Postbiotics in the Modulation of Human Oral Microbiota: A Randomized Controlled Clinical Trial - Wen Rui; Saiwei Zhong; Xiaoqian Li; Xuna Tang; Lijun Wang; Jingpeng Yang (Probiotics and Antimicrobial Proteins, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Reconstructing the tectonic evolution of the Mudanjiang Ocean: Metamorphic insights from the Heilongjiang Complex, NE China - Guang-Ming Sun; Xu-Ping Li; Hans-Peter Schertl; Jin-Rui Zhang; Xiao Wang; Wen-Yong Duan (Journal of Asian Earth Sciences, 2025)

Electrospun polylactic acid membranes containing Tartary buckwheat flavone extract for the preservation of green grapes - Jing Li; Liangping Zhang; Yuran Wang; Dayu Liu; Yongping Wen; Jian Wang; Rui Qi; Baohua Liu; Yin Zhang; Songzhi Xie (Food Chemistry, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Sensory characteristics and key odor-active compounds of oxidized Antarctic krill oil: A comparative study with oxidized fish oil - Gui-Mei Dong; Rui-Ying Wang; Fa-Wen Yin; De-Yang Li; Lei Qin; Da-Yong Zhou (Food Chemistry, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Ovotransferrin, an alternative and potential protein for diverse food and nutritional applications - Fengge Wen; Runxuan Chen; Mengxue Wang; Yihua Zhang; Wenjing Dong; Yuyu Zhang; Rui Yang (Critical Reviews in Food Science and Nutrition, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Screening and discovery of volatile allergenic components from artemisia ordosica in Yulin region of Northern China - Xiaoxue Mo; Cheng Wang; Yi Shan; Siqi Wang; Wen Yang; Zhaomin Xia; Zhanguo Qiao; Tao Zhang; Yuanyuan Ding; Rui Liu; Huaizhen He; Langchong He (Journal of Hazardous Materials, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Predicting glacial lake outburst susceptibility on the southern Tibetan Plateau with historical events and machine learning methods - Huan Liu; Zhewei Wang; Hong Wen; Nisong Pei; Zuqi Xia; Rui Bian; Song Ma; Ling Tao (Natural Hazards, 2025)

Recycling traditional Chinese medicine residues: a review - Xiaowei Wu; Dai Dai; Na Li; Haixin Zheng; Cuixia Wang; Weixiong Lin; Liaoyuan Liu; Zheng Zhang; Jörg Rinklebe; Carol Sze Ki Lin; Wen Rui; Chong Li (Environmental Chemistry Letters, 2025)
Traditional Chinese medicine has a rich history in the diagnosis and treatment of diseases, yet the disposal of medicine residues by incineration and landfilling is challenging. Here we review methods to recycle Chinese medicine residues with focus on challenges, recycling solutions, and case studies. Cases studies include extraction of bioactive compounds, use as feed additives, and biochar-based materials. We observed that residues from single-compound medicines are easier to extract and recycle into animal feed additives or adsorbents. Technical and economic analysis show that the valorisation of single-compound medicine residues is profitable. For instance, the re-extraction cost of flavonoids is 25.8–36.6% lower than the market price, and the cost as feed additives represents 14.7% of the market prices.

An integrated metabolomics-chemometrics strategy for discovering and characterizing potent anti-tyrosinase activity markers in functional tea Nelumbinis stamen - Yang Liu; Shujing Chen; Xue Meng; Jiake Wen; Rui Wang; Chengda Zhang; Kunze Du; Jin Li; Yanxu Chang (Food Bioscience, 2025)

One-step forming strategy of highly stable Li4SiO4 for low-concentration CO2 capture - Yu Zhang; Shuo Chen; Shikun Wen; Jiaojiao Li; Rui Yang; Liang Huang; Junya Wang; Ping Ning; Qiang Wang (Chemical Engineering Journal, 2025)

Inversion of Stress Redistribution Based on Focal Mechanism Solutions: A Case Study of the Dongtan Coal Mine - Kai Zhan; Hao Luo; Rui Xu; Xiaotao Wen; Cong Wang (Rock Mechanics and Rock Engineering, 2025)

Enhanced Microseismic Event Localization in Coal Mines Using the EDDI-Based Cross-Correlation Stacking Method - Kai Zhan; Xuben Wang; Xiaotao Wen; Rui Xu; Chao Kong; Chao Wang (Rock Mechanics and Rock Engineering, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Glycine betaine and MiWRKY53 enhance antioxidant capacity and disease resistance against Colletotrichum gloeosporioides in mango fruit - Xiaomin Niu; Yuxin Hu; Xin Wang; Rui Li; Wen Li; Yuanzhi Shao (Postharvest Biology and Technology, 2025)

Design and FPGA implementation of a zero IF I/Q blind calibration algorithm - Yongbo Liao; Lang Li; Linhan Li; Jiangshan Liang; Mengyou Li; Rui Chen; Xiongfei Chen; Menghao Wang; Wu Wen (Next Research, 2025)

Sinomenine synergistically enhances 5-Fu anticancer effects in oral cancer through modulating the miR-140-5p-PDK1-anaerobic glycolysis pathway - Dongmei Wang; Rui Wang; Hui Sun; Zhi Wen (Food and Chemical Toxicology, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Ensemble framework for multistep carbon emission prediction: an improved Bi-LSTM model based on the Bayesian optimization algorithm and two-stage decomposition - Qi Song; Yu-Long Bai; Rui Wang; Xiao-Xin Yue; Wen-Hui Liu (Stochastic Environmental Research and Risk Assessment, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

Modification effect of healthy lifestyle among solid fuels and mild cognitive impairment in middle-aged and older adults: A prospective cohort study - Jie He; Rui Yang; Kangkang Zhong; Chuanting Wen; Xuechun Liu; Yan Wang; Qi Zhong (NeuroToxicology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Co-culture fermentation of Debaryomyces hansenii and Bacillus atrophaeus alleviates quality deterioration of litchi fruit by ameliorating microbial community diversity and composition - Zhen Li; Yu Wang; Rui Li; Yuxin Hu; Xin Wang; Wen Li; Yuanzhi Shao (Food Microbiology, 2025)

Synergy between aerated drip and biodegradable film enhances sustainable maize production in arid oasis - Yonghui Liang; Mei Wu; Jinzhu Zhang; Zhanli Ma; Yue Han; Yue Wen; Rui Chen; Jian Liu; Haiqiang Li; Zhenhua Wang (European Journal of Agronomy, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Unveiling the nonlinear relationships and co-mitigation effects of green and blue space landscapes on PM2.5 exposure through explainable machine learning - Wei Cao; Liyan Wang; Rui Li; Wen Zhou; Deshun Zhang (Sustainable Cities and Society, 2025)

Transcriptome profiling in peanut (Arachis hypogaea) in response to biotic stress produce by Bacillus amyloliquefaciens TA-1 - Wang Chen; Taswar Ahsan; Di Han; Wen-Rui Wang; Si-Tong Du; Chao-Qun Zang; Yu-Qian Huang; Ejaz Hussain Siddiqi (Plant Gene, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Enhancing thermal conductivity, electromagnetic interference shielding, and joule heating in polyether ether ketone composites using three-dimensional scaly carbon fibre structures and structural optimisation - Yifan Wang; Fengyu Wen; Yashu He; Lin Cheng; Haoyuan Tan; Jierun Ma; Pengbo Lian; Yuxuan Gu; Rui Chen; Jianxin Mu (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Insight into distribution and composition of nonhuman N-Glycans in mammalian organs via MALDI-TOF and MALDI-MSI - Rui-Rui Guo; Bram Heijs; Wen-Jun Wang; Manfred Wuhrer; Li Liu; Guinevere S.M. Lageveen-Kammeijer; Josef Voglmeir (Carbohydrate Polymers, 2025)

Bayesian Microseismic Localization Method Based on the Maximum Entropy Hamiltonian Monte Carlo Markov Chain Approach - Kai Zhan; Xuben Wang; Xiaotao Wen; Rui Xu; Chao Kong; Chao Wang (Rock Mechanics and Rock Engineering, 2025)

Experiment and Peridynamics Simulation on Failure Mechanical Behavior of Cylindrical Sandstone Containing Two Persisting Fissures Under Conventional Triaxial Compression - Sheng-Qi Yang; Heng Li; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Wen-Ling Tian; Yun-Jin Hu; Yong Niu (Rock Mechanics and Rock Engineering, 2025)

Effect of Powdery Mildew Pathogen Inoculation on Gene Expression Levels and Root Microbial Community Structures in Bottle Gourd and Pumpkin Seedlings - Jian Zhang; Wen-Wen Wang; Peng-Cheng Wang; Rui Xia; Tong-Chun Gao (Journal of Soil Science and Plant Nutrition, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

Alkaloids from Dendrobium nobile and their anti-inflammatory activities - Zao-Yu Xu; Chao-Fan Wang; Wen Li; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

In-situ experiments of dynamic microscopic reaction for CO2-brine-carbonate system - Yulong Zhao; Yongchao Wang; Shaomu Wen; Liehui Zhang; Zhenglin Cao; Zihan Zhao; Wei Xiong; Cheng Cao; Rui Tang; Yunting Fan; Zehao Xie; Ruihan Zhang; et al. (Chemical Engineering Journal, 2025)

In-situ constructing 3D nanocarbon conduction conformal network on silicon anodes for high-performance sulfide-based all-solid-state batteries - Rui Huang; Ruilong Li; Shaobo Li; Wen Yang; Yu Bai; Zhenhua Wang; Kening Sun (Chemical Engineering Journal, 2025)

A Method for Coal Mine Seismic Network Detection Capability Calculation Based on Energy - Kai Zhan; Xiaotao Wen; Cong Wang; Chao Kong; Chao Wang; Rui Xu (Rock Mechanics and Rock Engineering, 2025)

A singular spectrum analysis-enhanced BiTCN-selfattention model for runoff prediction - Wen-chuan Wang; Feng-rui Ye; Yi-yang Wang; Miao Gu (Earth Science Informatics, 2025)

Enrichment characteristics of Cd and Hg and regulation of heavy metal transporter signaling in Pleurotus ostreatus - Qing Liu; Xiukun Zheng; Rui Du; Yuqiang Shao; Qing Wen; Xiaoye Shen; Fengqin Wang; Yuancheng Qi; Jinwen Shen; Yanru Hu (Science of The Total Environment, 2024)

Neolithization of Dawenkou culture in the lower Yellow River involved the demic diffusion from the Central Plain - Fen Wang; Rui Wang; Hao Ma; Wen Zeng; Yongsheng Zhao; Hao Wu; Zhongming Tang; Haifeng He; Hui Fang; Chuan-Chao Wang (Science Bulletin, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

A double-layer film based on the strategy of tannic acid-anthocyanin co-pigmentation and tannic-crosslinked-gelatin/−reduced Ag nanoparticles for beef preservation and monitoring - Rui Li; Haoyu Feng; Shancan Wang; Di Zhuang; Youhong Wen; Jie Zhu (Food Chemistry, 2024)

Concurrent removal of Fe(II), Cu(II), and Zn(II) cations from acid mine drainage by an industrial solid waste - Steel slag: Behaviors and mechanisms - Mingyuan Yang; Cunfang Lu; Shuo Zhang; Yelei Wang; Rui Xu; Min Zhang; Juan Wen; Zilong Li (Environmental Research, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

LGF SeismoLocator: A Deep Learning Model for Precision Microseismic Event Localization in Coal Mines - Kai Zhan; Xiaotao Wen; Rui Xu; Xuben Wang; Cong Wang; Ping Song; Chao Kong (Rock Mechanics and Rock Engineering, 2024)

Long-term effects of conventional cultivation on soil cation exchange capacity and base saturation in an arid desert region - Dengke Ma; Zhibin He; Wenzhi Zhao; Rui Li; Weihao Sun; Wen Wang; Pengfei Lin; Lemin Wei; Wenliang Ju (Science of The Total Environment, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

In-situ growth of Ni, Co-Prussian blue nanocubes on molten salt etched lamellar Ti3C2Tx/Ni for enhanced hybrid capacitive deionization - Wen Xi; Youfang Zhang; Jianing Hu; Zongchang Li; Rui Wang; Huanwen Wang; Yansheng Gong; Beibei He; Jun Jin (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Potential Applications of Blautia wexlerae in the Regulation of Host Metabolism - Wen Rui; Xiaoqian Li; Lijun Wang; Xuna Tang; Jingpeng Yang (Probiotics and Antimicrobial Proteins, 2024)

Numerical and laboratory experiments on the toppling behavior of a massive single block: a case study of the Furnas Reservoir, Brazil - Shu-wei Sun; Qiang Wen; Maria do Carmo Reis Cavalcanti; Xiao-rui Yang; Jia-qi Wang (Landslides, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Exposure to volatile organic compounds and growth indicators in adolescents: Unveiling the association and potential intervention strategies - Jingyi Ren; Xiaoya Sun; Zhenao Zhang; Huanting Pei; Yadong Zhang; Rui Wen; Simeng Qiao; Zidan Wang; Weican Zhang; Jinshi Zuo; Yuxia Ma (Journal of Hazardous Materials, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Contribution of the subducting slab on sulfur recycling: Insight from sulfur isotopic composition of lower crustal arc cumulates - Jingbo Zhang; Rui Wang; Wen-Rui Sun (Lithos, 2024)

Ultra-high capacity and anti-interference for Cr(VI) removal by tannin-polyvinylimine modified graphite carbon nitride - Wen Sun; Rui Wang; Lingfei Li; Jun Zhao; Bianhua Liu (Journal of Environmental Chemical Engineering, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Void-confinement effects of porous hollow nanostructures boost selectivity and durability of oxygen reduction reaction - Yingxiu Zhao; Ping Zhao; Wen Zhang; Xinyuan Zhou; Qiong Zhang; Yu Miao; Guang-Rui Xu; Lei Wang (Fuel, 2024)

Highly selective and sensitive immunoassays for flurogestone acetate analysis in goat milk: From rational hapten design and antibody production to assay development - Rui Liu; Xingya Sun; Yingjie Zhang; Peipei Li; Li Nan; Qing Shen; Kai Wen; Xuezhi Yu; Jianzhong Shen; Yantong Pan; Zhanhui Wang (Food Chemistry, 2024)

Assessing environmental and human health risks: Insight from the enantioselective metabolism and degradation of fenpropidin - Rui Li; Yingying Wu; Nuanhui Wen; Wenjie Wei; Wei Zhao; Yanhong Li; Liangliang Zhou; Minghua Wang (Environmental Pollution, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Highly nanostructured and carboxylated wood aerogel-based adsorption membrane reconstructed by grafting of polyacrylic acid for efficient removal of heavy-metal ions - Wen He; Bairen Wei; Shuang Liang; Rui Wang; Qiulin Ji; Gangzheng Hu; Wenxuan Li; Lei He; Juan Yu; Hongfei Zhu; Kaiyin Wang (Chemical Engineering Journal, 2024)

Molecular mechanisms and atmospheric implications of the simplest criegee intermediate and hydrochloric acid chemistry in the gas phase and at the aqueous interfaces - Chao Ding; Mingjie Wen; Tianlei Zhang; Zeyao Li; Rongrong Li; Rui Wang; Ting Ou; Fengmin Song; Qiang Zhang (Atmospheric Environment, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

A highly sensitive and colorimetric fluorescent probe for visualizing hydroxylamine in immune cells - Wei Du; Yang Tian; Yu-An Feng; Xiao-Wei Cong; Rui Tan; Ya-Wen Wang; Yu Peng (Analytica Chimica Acta, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Changes in the lithosphere, atmosphere, and ionosphere before and during the Mw = 7.7 Jamaica 2020 earthquake - Dedalo Marchetti; Kaiguang Zhu; Alessandro Piscini; Essam Ghamry; Xuhui Shen; Rui Yan; Xiaodan He; Ting Wang; Wenqi Chen; Jiami Wen; Yiqun Zhang; Yuqi Cheng; et al. (Remote Sensing of Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Recent advances of 2D materials in capacitive deionization - Jun Jin; Wen Xi; Zongchang Li; Jianing Hu; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Youfang Zhang (Desalination, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Climate and soil: Key Drivers of Plant Traits and Community Functional Differences in the Lakeshore Wetlands of Northern China - Rui Zhang; Zhichao Xu; Huamin Liu; Hongbo Yu; Feng Niu; Haitao Fang; Linqian Ma; Yunhao Wen; Lu Wen; Yi Zhuo; Lixin Wang (Wetlands, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Artemisia argyi H. Lév. & Vaniot: a comprehensive review on traditional uses, phytochemistry, and pharmacological activities - Wen-Jun Wei; Tao Guo; Gui-Min Xue; Rui Ma; Yuefei Wang; Zhe-Sheng Chen (Phytochemistry Reviews, 2024)

Suitability of reduced dose glucocorticoids therapy regimen for antibody-associated vasculitis patients with TB: a retrospective study - Rui Wen; Jingni Xiao; Ning Ding; Yong Zhong; Qiong Yuan; Jiali Li; Qi Wang; Hebin Xie; Jiao Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Variations in Column Concentration of Greenhouse Gases in China and Their Response to the 2015–2016 El Niño Event - Ningwei Liu; Lingjun Xia; Youjun Dou; Shaorou Dong; Jing Wen; Ying Wang; Rui Feng; Ruonan Wang; Yuhe Li (Journal of Meteorological Research, 2024)

Intestinal carcinogenicity screening of environmental pollutants using organoid-based cell transformation assay - Ziwei Wang; Shen Chen; Yuzhi Guo; Rui Zhang; Qi Zhang; Xinhang Jiang; Miao Li; Yue Jiang; Lizhu Ye; Xiaoyu Guo; Chuang Li; Guangtong Zhang; et al. (Archives of Toxicology, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Encapsulate Co3O4 within ultrathin graphene sheets to enhance peroxymonosulfate activation by tuning surface electronic structures - Taobo Huang; Rui An; Jie Li; Wen Liu; Xiuping Zhu; Haodong Ji; Ting Wang (Science of The Total Environment, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Effects of plastic film mulching on yield, water use efficiency, and nitrogen use efficiency of different crops in China: A meta-analysis - Tiantian Huang; Qianxiang Wu; Yangyang Yuan; Xintong Zhang; Ruiqi Sun; Rui Hao; Xiaohua Yang; Congfeng Li; Xiaoliang Qin; Fangqi Song; Charles O. Joseph; Wen Wang; et al. (Field Crops Research, 2024)

ZnS-coated Yb3+-doped perovskite quantum dots: A stable and efficient quantum cutting photon energy converter for silicon-based electronics - Yue Wang; Nan Ding; Donglei Zhou; Wen Xu; Rui Sun; Wei Li; Yuqi Wang; Liheng Sun; Songtao Hu; Hongwei Song (Chemical Engineering Journal, 2024)

Slope Stability Analysis under Heavy Rainfall Conditions Based on a Modified Green-Ampt Model - Yunxin Zheng; Zhiping Hu; Rui Wang; Xin Wen; Xiang Ren; Rui Pan (Water Resources Management, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effects of belt trusses on drift control of frame-core tube structures - Wen-Bo Wang; Hong-Song Hu; Rui-Tao Wang; Yi-Chao Gao; Zi-Xiong Guo (Engineering Structures, 2024)

Molten salt etching synthesis of Ti3C2Tx/Ni composites for highly efficient capacitive deionization - Wen Xi; Tianzhuo Guo; Zeren Xie; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Desalination, 2024)

Ultrafine FeCuAgCeGd–based high–entropy nanozyme: Preparation, catalytic mechanism, and point–of–care detection of dopamine in human serum - Rui Sheng; Yue Liu; Taimei Cai; Rong Wang; Gan Yang; Tao Wen; Fangjian Ning; Hailong Peng (Chemical Engineering Journal, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Topological spin-orbit-coupled fermions beyond rotating wave approximation - Han Zhang; Wen-Wei Wang; Chang Qiao; Long Zhang; Ming-Cheng Liang; Rui Wu; Xu-Jie Wang; Xiong-Jun Liu; Xibo Zhang (Science Bulletin, 2024)

Inferring the demographic history of Hexi Corridor over the past two millennia from ancient genomes - Jianxue Xiong; Rui Wang; Guoke Chen; Yishi Yang; Panxin Du; Hailiang Meng; Minmin Ma; Edward Allen; Le Tao; Hui Wang; Li Jin; Chuan-Chao Wang; et al. (Science Bulletin, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Chameleon-inspired supramolecular materials based on cucurbit[7]uril and viologens exhibiting full-color tunable photochromic behavior - Dong-Xue Xia; Xin Wang; Wen-Qi Sun; Rui-Lian Lin; Jing-Xin Liu; Ying-Wei Yang (Chemical Engineering Journal, 2024)

Ubiquitination-dependent protein homeostasis is critical for the thermotolerance of the economically valuable seaweed Pyropia haitanensis - Rui Zhao; Jian Wen; Kai Xu; Yan Xu; Dehua Ji; Chaotian Xie; Wenlei Wang (Aquaculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Performance of round-ended CFST columns under combined actions of eccentric compression and impact loads - Hui Zhao; Shengqi Mei; Rui Wang; Xu Yang; Wen-Da Wang; Wensu Chen (Engineering Structures, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Mitigating cadmium accumulation in dicotyledonous vegetables by iron fertilizer through inhibiting Fe transporter IRT1-mediated Cd uptake - Zhong-Rui Xu; Ting-Ting You; Wen-Yi Liu; Kang Ye; Fang-Jie Zhao; Peng Wang (Chemosphere, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Diterpenolignans and cephalotane diterpenoids from Cephalotaxus oliveri mast. with antitumor activity - Chunyu Jiang; Zimeng Han; Wen Sun; Jiayi Tan; Guiwen Gao; Xuan Wang; Huiming Hua; Rui Zhao; Tong Han (Phytochemistry, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Evolution of Silurian phytogeography, with the first report of Aberlemnia (Rhyniopsida) from the Pridoli of West Junggar, Xinjiang, China - Bing-Cai Liu; Rui-Wen Zong; Kai Wang; Jiao Bai; Yi Wang; Hong-He Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Degradation profile of environmental pollutant 17β-estradiol by human intestinal fungus Aspergillus niger RG13B1 and characterization of genes involved in its degradation - Qi-Meng Zhu; Chao Wang; Jing-Wen Liu; Rui Zhang; Xiu-Lan Xin; Juan Zhang; Cheng-Peng Sun; Xiao-Chi Ma (Journal of Hazardous Materials, 2024)

Square-wave alternating voltage driving promotes nanowire-assisted electroporation inactivation and fouling resistance of pathogenic bacteria for water disinfection - Ying-Wen Lu; Yang Wang; Yi-Rui Liu; Hai Liu (Chemical Engineering Journal, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

Late Cretaceous bimodal volcanic rocks in Shuanghu induced by lithospheric delamination beneath the Southern Qiangtang, Tibet - Ding-Jun Wen; Xiumian Hu; Timothy Chapman; Gang Zeng; An-Lin Ma; Rui-Qiang Wang (Lithos, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Rapid LC-MS/MS detection of 25-hydroxyvitamin D in dried blood spots - Hai-Bo Wang; Xuan Xiao; Wen Dai; Rui Peng; Juan Le; Yu-Qi Feng; Shao-Ting Wang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Adaptability of wheat to future climate change: Effects of sowing date and sowing rate on wheat yield in three wheat production regions in the North China Plain - Pengfei Wen; Qiongru Wei; Liang Zheng; Zhanxu Rui; Mengjiao Niu; Chenkai Gao; Xiaokang Guan; Tongchao Wang; Shuping Xiong (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Self-supportive Pd0.2Ni58Fe30O11.8 nanowires for solar-driven self-powered water/seawater splitting with large current density - Guang-Rui Xu; Ning Zhang; Qiyan Sun; Wen Zhang; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2023)

Molecular insights of condensate trapping mechanism in shale oil reservoirs and its implications on lean gas enhanced oil recovery - Shihao Wang; Hongwei Zhang; Bikai Jin; Rui Qiao; Xian-Huan Wen (Chemical Engineering Journal, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Molecular dynamics simulation on the dissolution and diffusion characteristics of FeCrAl alloy in liquid LBE - Lu Xie; Guang Da Wu; Qing Peng; Wen Rui Wang (Annals of Nuclear Energy, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

IFN-γ promotes PANoptosis in Pasteurella multocida toxin-induced pneumonia in mice - Hang Xiao; Qin Zhao; Jianlin Yuan; Wei Liang; Rui Wu; Yiping Wen; Senyan Du; Yiping Wang; Shan Zhao; Yifei Lang; Qigui Yan; Xiaobo Huang; et al. (Veterinary Microbiology, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Effect of Triton X-100 on Shiraia laccase production and its application in triclosan biodegradation - Rui Peng Cong; Yan Hua Guo; Jian Qin Zhou; Jian Wen Wang (Sustainable Chemistry and Pharmacy, 2023)

Controllable solvent treatment of fluorinated graphite for high power density and low cathode swelling lithium primary batteries - Sen Ma; Wen Liu; Daoming Zhang; Cheng Yang; Ying Luo; Xiaobing Lou; Rui Guo; Yong Wang; Jingying Xie (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Experimental study on microstructural modification of coal by liquid CO2 extraction - Hu Wang; Hu Wen; Zhenbao Li; Rui Liang; Fengshuang Wang; Shixing Fan; Rijun Li (Fuel, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Immobilization of Bacillus Thuringiensis and applicability in removal of sulfamethazine from soil - Shengfang Wen; Hunan Liu; Rui Yang; Lanjun Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Environmental Pollution, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Emerging two-dimensional (2D) MXene-based nanostructured materials: Synthesis strategies, properties, and applications as efficient pseudo-supercapacitors - Rui Wang; Won Young Jang; Wen Zhang; Ch. Venkata Reddy; Raghava Reddy Kakarla; Changping Li; Vijai Kumar Gupta; Jaesool Shim; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2023)

Selective pollutant degradation with a novel persulfate activation cell resistant to environmental interference - Hui-Shan Meng; Shu-Zhen He; Mei-Mei Wang; Jia-Rui Xi; Jia-Tai Wen; Hong-Wei Luo; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Iron-rich red mud and iron oxide-modified biochars: A comparative study on the removal of Cd(II) and influence of natural aging processes - Huabin Wang; Dingxiang Chen; Yi Wen; Yong Zhang; Ying Liu; Rui Xu (Chemosphere, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Differential effects of petroleum-based and bio-based microplastics on anaerobic digestion: A review - Zezhou Shang; Rui Wang; Xiyi Zhang; Yongle Tu; Chenjing Sheng; Huan Yuan; Lei Wen; Yulu Li; Jing Zhang; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; et al. (Science of The Total Environment, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Surface-enhanced Raman spectroscopy charged probes under inverted superhydrophobic platform for detection of agricultural chemicals residues in rice combined with lightweight deep learning network - Shizhuang Weng; Le Tang; Mengqing Qiu; Jinghong Wang; Yehang Wu; Rui Zhu; Cong Wang; Pan Li; Wen Sha; Dong Liang (Analytica Chimica Acta, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Multiple evaluations of atmospheric behavior between Criegee intermediates and HCHO: Gas-phase and air-water interface reaction - Tianlei Zhang; Mingjie Wen; Chao Ding; Yongqi Zhang; Xiaohui Ma; Zhuqing Wang; Makroni Lily; Junhai Liu; Rui Wang (Journal of Environmental Sciences, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Influence of aboveground structure on connected underground structure seismic response within an integrated system - Wen-Ting Li; Rui Wang; Jian-Min Zhang (Tunnelling and Underground Space Technology, 2023)

Thickness-dependent release of microplastics and phthalic acid esters from polythene and biodegradable residual films in agricultural soils and its related productivity effects - Aimee Grace Uzamurera; Peng-Yang Wang; Ze-Ying Zhao; Xiu-Ping Tao; Rui Zhou; Wen-Ying Wang; Xiao-Bin Xiong; Song Wang; Kiprotich Wesly; Hong-Yan Tao; You-Cai Xiong (Journal of Hazardous Materials, 2023)

Corrigendum to “Self-supported PdNi dendrite on Ni foam for improving monohydric alcohol and polyhydric alcohols electrooxidation” [Fuel 326 (2022) 125083] - Ning Zhang; Jing Wang; Wen Zhang; Yingxiu Zhao; Zemeng Dong; Zexing Wu; Guang-Rui Xu; Lei Wang (Fuel, 2023)

Metal-carbonate interface promoted activity of Ag/MgCO3 catalyst for aqueous-phase formaldehyde reforming into hydrogen - Qiaojuan Wang; Jianyue Wang; Wenjuan Rui; Dan Yang; Xiaoyue Wan; Chunmei Zhou; Renhong Li; Wen Liu; Yihu Dai; Yanhui Yang (Fuel, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Highly efficient aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid over halloysite nanotubes-templated nitrogen-doped carbon supported bimetallic AuPd catalyst - Fang Wang; Changhao Yan; Rui Jiang; Yao Chen; Yanan Wei; Yu Cao; Wen Guan; Pengwei Huo; Yunlei Zhang (Applied Clay Science, 2023)

Morphological alterations in C57BL/6 mouse intestinal organoids as a tool for predicting chemical-induced toxicity - Ziwei Wang; Shen Chen; Yaqin Pang; Lizhu Ye; Qi Zhang; Xinhang Jiang; Rui Zhang; Miao Li; Zhanyu Guo; Yue Jiang; Daochuan Li; Xiumei Xing; et al. (Archives of Toxicology, 2023)

Exposure to cadmium induced gut antibiotic resistance genes (ARGs) and microbiota alternations of Babylonia areolata - Wang Zhao; Qian Han; Rui Yang; Weigeng Wen; Zhenghua Deng; Huan Li; Zhongming Zheng; Zhenhua Ma; Gang Yu (Science of The Total Environment, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Identification of three Streptomyces strains and their antifungal activity against the rubber anthracnose fungus Colletotrichum siamense - Jinhong Wang; Rui Wang; Jing Gao; Huanqing Liu; Wen Tang; Zhiqiang Liu; Xiaoyu Li (Journal of General Plant Pathology, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Axial compression behaviour of round-ended recycled aggregate concrete-filled steel tube stub columns (RE-RACFST): Experiment, numerical modeling and design - Hui Zhao; Wen-Hao Zhang; Rui Wang; Chuan-Chuan Hou; Dennis Lam (Engineering Structures, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Development of quantitative wastewater surveillance models facilitated the precise epidemic management of COVID-19 - Songzhe Fu; Fenglan He; Rui Wang; Wentao Song; Qingyao Wang; Wen Xia; Zhiguang Qiu (Science of The Total Environment, 2023)

Influence of collaborative disposal of sewage sludge in the fly ash partitioning and PM10 emission from a subcritical coal-fired boiler - Tianyu Liu; Chang Wen; Ke Zhou; Changkang Li; Youjian Zhu; Dapeng Wang; Rui Li; Zhenqi Jing (Fuel, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

One-dimensional copper bromide based inorganic-organic hybrids as fuels for hypergolic bipropellants with hydrogen peroxide as oxidizer - Ya-Jie Wang; Xu-Yang Wang; Hong Xu; Wei-Wei Ren; Rui Pang; Li Yang; Wen-Chao Tong; Qian-You Wang; Shuang-Quan Zang (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Characteristics of stress, crack evolution, and energy conversion of anchored granite containing two preexisting fissures under uniaxial compression - Wen Guanping; Hu Jianhua; Wang Jie; Yang Dongjie; Xiang Rui (Bulletin of Engineering Geology and the Environment, 2023)

The influence of hapten spacer arm length on antibody response and immunoassay development - Yuchen Bai; Rui Liu; Leina Dou; Weilin Wu; Wenbo Yu; Kai Wen; Xuezhi Yu; Jianzhong Shen; Zhanhui Wang (Analytica Chimica Acta, 2023)

Molecular characterization of a novel victorivirus isolated from the phytopathogenic fungus Phaeobotryon rhois - Ying Zhao; Hongyan Du; Yuanyuan Liu; Rongrong Zhong; Zhengzhe Guan; Ganlin Wang; Yuanyuan Zhang; Chenxing Wei; Mengjiao Wang; Xinru Wan; Rui Zang; Caiyi Wen; et al. (Archives of Virology, 2023)

B-YOLOX-S: A Lightweight Method for Underwater Object Detection Based on Data Augmentation and Multiscale Feature Fusion - Jun Wang; Shuman Qi; Chao Wang; Jin Luo; Xin Wen; Rui Cao (Journal of Marine Science and Engineering, 2022)
With the increasing maturity of underwater agents-related technologies, underwater object recognition algorithms based on underwater robots have become a current hotspot for academic and applied research. However, the existing underwater imaging conditions are poor, the images are blurry, and the underwater robot visual jitter and other factors lead to lower recognition precision and inaccurate positioning in underwater target detection. A YOLOX-based underwater object detection model, B-YOLOX-S, is proposed to detect marine organisms such as echinus, holothurians, starfish, and scallops. First, Poisson fusion is used for data amplification at the input to balance the number of detected targets. Then, wavelet transform is used to perform Style Transfer on the enhanced images to achieve image restoration. The clarity of the images and detection targets is further increased and the generalization of the model is enhanced. Second, a combination of BIFPN-S and FPN is proposed to fuse the effective feature layer obtained by the Backbone layer to enhance the detection precision and accelerate model detection. Finally, the localization loss function of the prediction layer in the network is replaced by EIoU_Loss to heighten the localization precision in detection. Experimental results comparing the B-YOLOX-S algorithm model with mainstream algorithms such as FasterRCNN, YOLOV3, YOLOV4, YOLOV5, and YOLOX on the URPC2020 dataset show that the detection precision and detection speed of the algorithm model have obvious advantages over other algorithm networks. The average detection accuracy mAP value is 82.69%, which is 5.05% higher than the benchmark model (YOLOX-s), and the recall rate is 8.03% higher. Thus, the validity of the algorithmic model proposed in this paper is demonstrated.

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Evaluating the stability of Outang landslide in the Three Gorges Reservoir area considering the mechanical behavior with large deformation of the slip zone - Junbiao Yan; Zongxing Zou; Rui Mu; Xinli Hu; Jincheng Zhang; Wen Zhang; Aijun Su; Jinge Wang; Tao Luo (Natural Hazards, 2022)

Synergistic Effect and Mechanism of Apoptosis Induction by Morphine and the HIV-1gp120V3 Loop in Hippocampal Neurons - Xueqin Yan; Zheng Gong; Rui Pan; Huili Wang; Haijie Tang; Hanyang He; Saixian Wen; Yongmei Fu; Jun Dong (Journal of Neuroimmune Pharmacology, 2022)

Chlorogenic acid, a natural product as potential inhibitor of COVID-19: virtual screening experiment based on network pharmacology and molecular docking - Wen-Xiang Wang; Ying-Rui Zhang; Shi-Ying Luo; Yun-Sen Zhang; Yi Zhang; Ce Tang (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Epigallocatechin‐3‐gallate inhibits replication of white spot syndrome virus in the freshwater crayfish Procambarus clarkii - Yitong Zhang; Jinxuan Wen; Yao Xu; Hao Wang; Liqun Lu; Rui Song; Jixing Zou (Journal of Fish Diseases, 2022)
The freshwater crayfish Procambarus clarkii is native to North America and Mexico, and it was introduced to China in 1929. The production and consumption of P. clarkii in China are the highest worldwide, reaching 208.96 million tons in 2020. The white spot syndrome virus (WSSV) is a major pathogen that affects shrimp, crayfish, crabs and lobsters, and it has caused widespread loss to the P. clarkii industry. Epigallocatechin‐3‐gallate (EGCG), a small‐molecule compound, has a multitude of biological functions and the ability to bind to the 37 kDa/67 kDa laminin receptor ( LamR ). EGCG has potential antiviral effects against WSSV. In this study, we evaluated the potential anti‐WSSV applications of EGCG in P. clarkii . We demonstrated that various concentrations (10 μg/g·bw, 20 μg/g·bw and 40 μg/g·bw) of EGCG can suppress WSSV infection in P. clarkii . Histopathological examination revealed no characteristic pathological changes due to EGCG administration in P. clarkii tissues. Furthermore, pharmacokinetics studies of EGCG in P. clarkii revealed its rapid absorption (T max = 2 h), and the peak concentrations of EGCG were 73.78 µg/g in the liver and 24.87 µg/g in the muscle. Our results indicate the high potential applications of EGCG against WSSV in P. clarkii .

Evaluation of suitable qRT-PCR normalization genes for various citrus rootstocks - Wen He; Rui Xie; Huan Li; Yan Wang; Qing Chen; Yuanxiu Lin; Yunting Zhang; Ya Luo; Yong Zhang; Haoru Tang; Xiaorong Wang (Plant Biotechnology Reports, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

Microbial ecology of sulfur cycling near the sulfate–methane transition of deep‐sea cold seep sediments - Wen‐Li Li; Xiyang Dong; Rui Lu; Ying‐Li Zhou; Peng‐Fei Zheng; Dong Feng; Yong Wang (Environmental Microbiology, 2021)
Summary Microbial sulfate reduction is largely associated with anaerobic methane oxidation and alkane degradation in sulfate–methane transition zone (SMTZ) of deep‐sea cold seeps. How the sulfur cycling is mediated by microbes near SMTZ has not been fully understood. In this study, we detected a shallow SMTZ in three of eight sediment cores sampled from two cold seep areas in the South China Sea. One hundred ten genomes representing sulfur‐oxidizing bacteria (SOB) and sulfur‐reducing bacteria (SRB) strains were identified from three SMTZ‐bearing cores. In the layers above SMTZ, SOB were mostly constituted by Campylobacterota, Gammaproteobacteria and Alphaproteobacteria that probably depended on nitrogen oxides and/or oxygen for oxidation of sulfide and thiosulfate in near‐surface sediment layers. In the layers below the SMTZ, the deltaproteobacterial SRB genomes and metatranscriptomes revealed CO 2 fixation by Wood–Ljungdahl pathway, sulfate reduction and nitrogen fixation for syntrophic or fermentative lifestyle. A total of 68% of the metagenome assembled genomes were not adjacent to known species in a phylogenomic tree, indicating a high diversity of bacteria involved in sulfur cycling. With the large number of genomes for SOB and SRB, our study uncovers the microbial populations that potentially mediate sulfur metabolism and associated carbon and nitrogen cycles, which sheds light on complex biogeochemical processes in deep‐sea environments.

Optimizing staggered-grid finite-difference method based on the least-squares combination of the square window function - Chao-pu Chen; Hong Liu; Zhi-yang Wang; Wen-lei Bai; Cheng-fang Zhang; Zi-rui Meng (Applied Geophysics, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Estimation of the vertically integrated leaf nitrogen content in maize using canopy hyperspectral red edge parameters - Pengfei Wen; Zujiao Shi; Ao Li; Fang Ning; Yuanhong Zhang; Rui Wang; Jun Li (Precision Agriculture, 2021)

Analyzing and optimizing yield formation of tomato introgression lines using plant model - Mengzhen Kang; Xiujuan Wang; Rui Qi; Zhi-Qi Jia; Philippe de Reffye; San-Wen Huang (Euphytica, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Simvastatin Enhances Muscle Regeneration Through Autophagic Defect-Mediated Inflammation and mTOR Activation in G93ASOD1 Mice - Yafei Wang; Lin Bai; Shuai Li; Ya Wen; Qi Liu; Rui Li; Yaling Liu (Molecular Neurobiology, 2021)

Development of global soil erosion research at the watershed scale: a bibliometric analysis of the past decade - Xuan Huang; Kai-Rui Wang; Yu-wen Zou; Xin-Chun Cao (Environmental Science and Pollution Research, 2021)

Estimates on thermal impact of gas-line and alleviating effect of countermeasures in patchy permafrost of northwestern China - Rui Shi; Xu Wang; Zhi Wen; Desheng Li (Bulletin of Engineering Geology and the Environment, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

The role of hydrous mantle-derived magmas in the generation of Late Cretaceous granitoids in the Gangdese batholith: insights from the Shanba and Zongga plutons in the southern Lhasa subterrane, Tibet - Rui-Qiang Wang; Jian-Sheng Qiu; Ding-Jun Wen; Hang Xu (Mineralogy and Petrology, 2021)

Characterization of TEMPO-oxidized chitin nanofibers with various oxidation times and its application as an enzyme immobilization support - Rui Chen; Wen-Can Huang; Wei Wang; Xiangzhao Mao (Marine Life Science & Technology, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Constructed wetlands integrated with microbial fuel cells for COD and nitrogen removal affected by plant and circuit operation mode - Huiyang Wen; Hui Zhu; Baixing Yan; Brian Shutes; Xiangfei Yu; Rui Cheng; Xin Chen; Xinyi Wang (Environmental Science and Pollution Research, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

Redescription of five tintinnine ciliates (Alveolata: Ciliophora: Oligotrichea) from coastal waters of Qingdao, China - Yang Bai; Rui Wang; Wen Song; Toshikazu Suzuki; Xiaozhong Hu (Marine Life Science & Technology, 2020)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

Two-Dimensional Discrepancies in Fracture Geometric Factors and Connectivity Between Field-Collected and Stochastically Modeled DFNs: A Case Study of Sluice Foundation Rock Mass in Datengxia, China - Wen Zhang; Rui Fu; Chun Tan; Zhifa Ma; Ying Zhang; Shengyuan Song; Peihua Xu; Shuonan Wang; Yunpeng Zhao (Rock Mechanics and Rock Engineering, 2020)

Effects of structural planes on rockburst position with respect to tunnel cross-sections: a case study involving a railway tunnel in China - Lei Hu; Xia-Ting Feng; Ya-Xun Xiao; Rui Wang; Guang-Liang Feng; Zhi-Bin Yao; Wen-Jing Niu; Wei Zhang (Bulletin of Engineering Geology and the Environment, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Benefit–risk assessment of commonly consumed fish species from South China Sea based on methyl mercury and DHA - Ping Wang; Shao-wei Chen; Zi-hui Chen; Wei-lun Huo; Rui Huang; Wei-xiong Huang; Jie-wen Peng; Xing-fen Yang (Environmental Geochemistry and Health, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Identification of genes revealed differential expression profiles and lignin accumulation during leaf and stem development in tea plant (Camellia sinensis (L.) O. Kuntze) - Yong-Xin Wang; Rui-Min Teng; Wen-Li Wang; Ying Wang; Wei Shen; Jing Zhuang (Protoplasma, 2019)

Complete mitochondrial genome of Hemiculter tchangi (Cypriniformes, Cyprinidae) - Yuanchao Zou; Ting Liu; Qian Li; Zhengyong Wen; Chuanjie Qin; Rui Li; Deshou Wang (Conservation Genetics Resources, 2019)

Differential deployment of sanctioning mechanisms by male and female host trees in a gynodioecious fig–wasp mutualism - Xiao‐Wei Zhang; Derek W. Dunn; Xiao‐Lan Wen; Bao‐Fa Sun; Rui‐Wu Wang (Ecology, 2019)
In some insect nursery pollination mutualisms, plant hosts impose net costs to uncooperative “cheater” symbionts. These “sanctions” promote mutualism stability but their precise adaptive nature remains unclear. In fig–wasp mutualisms host trees ( Ficus spp.) are only pollinated by female agaonid wasps whose larvae only use galled fig flowers as food. In actively pollinated systems, if wasps fail to pollinate, sanctions can result via fig abortion, killing all wasp offspring, or by increased offspring mortality within un‐aborted figs. These sanctions result from selective investment to pollinated inflorescences, a mechanism present in almost all angiosperms. To more fully understand how selective investment functions as sanctions requires the measurement of variation in their costs and benefits to both hosts and symbionts. Gynodioecious fig‐tree–fig‐wasp mutualisms are particularly suitable for this because pollen and wasps are produced only in the figs of “male” trees and seeds only in the figs of “female” trees. Male and female trees thus incur different net costs of pollen absence, and costs of sanctions to pollen‐free “cheater” wasps only occur in male trees. We used the actively pollinated host tree Ficus hispida and introduced into male and female figs either 1, 3, 5, 7, or 9 all pollen‐laden “cooperative” (P+) or all pollen‐free “cheater” (P−) wasps. Abortion in both male and female trees was highest in P− figs, with P− fig abortion higher in females (~90%) than in males (~40%). Fig abortion was negatively associated with foundress number mainly in P+ figs; in P− figs abortion was only weakly associated with the number of “cheater” wasps, especially in female figs. In un‐aborted male figs, wasp offspring mortality was higher in P− figs than in P+ figs, and in P− figs correlated positively with foundress (cheater) number. Increased offspring mortality was biased against female wasp offspring and likely resulted from reduced larval nutrition in unpollinated flowers. Variation in selective investment to P− figs thus reflects costs and benefits of pollen absence/presence to hosts, variation that translates directly to net costs to cheater wasps.

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Multi-year assessment of paralytic shellfish toxins in hard clam species along the coastline of Jiangsu Province, China - Xinzhi Wang; Hao Wu; Ying Cheng; Hongmei Wen; Rui Liu; Libao Wang; Chenxiao Shan; Chuan Chai (Acta Oceanologica Sinica, 2019)

Characterization and phylogenetic analysis of the complete maternal mitochondrial genome of freshwater mussel Aculamprotula scripta (Bivalvia: Unionidae: Unioninae) - Rui-Wen Wu; Sa Wang; Yi-Tong Liu; Xiong-Jun Liu; Chun-Hua Zhou; Shan Ouyang; Xiao-Ping Wu (Conservation Genetics Resources, 2018)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of the hybrid of Acipenser dabryanus (♀) × A. schrenckii (♂) and its phylogeny - Yuanchao Zou; Junying Zhang; Zhengyong Wen; Chuanjie Qin; Yongming Wang; Rui Li; Zemin Qi (Conservation Genetics Resources, 2018)

Morphology and molecular phylogeny of two new species of Spirostrombidium (Ciliophora, Oligotrichia), with a key to the species of Spirostrombidium - Rui Wang; Wen Song; Zhenzhen Yi; Khaled A. S. Al-Rasheid; Xiaozhong Hu (Systematics and Biodiversity, 2018)

An assessment of air-quality monitoring station locations based on satellite observations - Tao Yu; Wen Wang; Pubu Ciren; Rui Sun (International Journal of Remote Sensing, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Health Risk Assessment for Local Residents from the South China Sea Based on Mercury Concentrations in Marine Fish - Shao-wei Chen; Zi-hui Chen; Ping Wang; Rui Huang; Wei-lun Huo; Wei-xiong Huang; Xing-fen Yang; Jie-wen Peng (Bulletin of Environmental Contamination and Toxicology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Cryobiotechnology of forest trees: recent advances and future prospects - Jing-Wei Li; Elif Aylin Ozudogru; Jiao Li; Min-Rui Wang; Wen-Lu Bi; Maurizio Lambardi; Qiao-Chun Wang (Biodiversity and Conservation, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Waterlogging risk assessment based on self-organizing map (SOM) artificial neural networks: a case study of an urban storm in Beijing - Wen-li Lai; Hong-rui Wang; Cheng Wang; Jie Zhang; Yong Zhao (Journal of Mountain Science, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

Reply to the comments on “Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust” - Rui Wang; William J. Collins; Roberto F. Weinberg; Jeremy P. Richards; Wen-yan He (Contributions to Mineralogy and Petrology, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Loss of preferred habitat and pollen limitation threatens reproduction in a rare mountain Paeonia delavayi - Wei Li; Wen-wen Pan; Rui Tan; Juan Wang (Journal of Mountain Science, 2016)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Functional analysis of a chitinase gene during the larval-nymph transition in Panonychus citri by RNA interference - Wen-Kai Xia; Xiao-Min Shen; Tian-Bo Ding; Jin-Zhi Niu; Rui Zhong; Chong-Yu Liao; Ying-Cai Feng; Wei Dou; Jin-Jun Wang (Experimental and Applied Acarology, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Impact of temperature variation between adjacent days on childhood hand, foot and mouth disease during April and July in urban and rural Hefei, China - Jian Cheng; Rui Zhu; Zhiwei Xu; Jinju Wu; Xu Wang; Kesheng Li; Liying Wen; Huihui Yang; Hong Su (International Journal of Biometeorology, 2016)

Phylogenetic analysis reveals that Japanese encephalitis virus genotype III is still prevalent in swine herds in Sichuan province in China - Rui Wu; Qiao Wang; Hongming Liu; Chunxia Chai; Bo He; Xiaobo Huang; Yiping Wen; Xintian Wen; Qiguai Yan; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Treatment of retinitis pigmentosa due to MERTK mutations by ocular subretinal injection of adeno-associated virus gene vector: results of a phase I trial - Nicola G. Ghazi; Emad B. Abboud; Sawsan R. Nowilaty; Hisham Alkuraya; Abdulrahman Alhommadi; Huimin Cai; Rui Hou; Wen-Tao Deng; Sanford L. Boye; Abdulrahman Almaghamsi; Fahad Al Saikhan; Hassan Al-Dhibi; et al. (Human Genetics, 2016)

Azimuthal cement evaluation with an acoustic phased-arc array transmitter: numerical simulations and field tests - Xiao-Hua Che; Wen-Xiao Qiao; Xiao-Dong Ju; Rui-Jia Wang (Applied Geophysics, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Activin A can induce definitive endoderm differentiation from human parthenogenetic embryonic stem cells - Zhiqiang Wang; Wenliang Li; Tianxing Chen; Jun Yang; Zhengqi Wen; Xinmin Yan; Tao Shen; Rui Liang (Biotechnology Letters, 2015)

Marinactinospora endophytica sp. nov., isolated from a medicinal plant - Min-Jiao Liu; Thi-Nhan Khieu; Rui Gao; Wael N. Hozzein; Hong-Fei Wang; Wei Yang; Salam Nimaichand; Zhi Xiong; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Identification and validation of suitable reference genes for RT-qPCR analysis in mouse testis development - Zu-Kang Gong; Shuang-Jie Wang; Yong-Qi Huang; Rui-Qiang Zhao; Qi-Fang Zhu; Wen-Zhen Lin (Molecular Genetics and Genomics, 2014)

Semicarbazide – from state-of-the-art analytical methods and exposure to toxicity: a review - Wen-Rui Tian; Ya-Xin Sang; Xiang-Hong Wang (Food Additives & Contaminants: Part A, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

Identification of a novel fumarase C from Streptomyces lividans TK54 as a good candidate for l-malate production - Rui-Rui Su; Ao Wang; Song-Tao Hou; Peng Gao; Guo-Ping Zhu; Wen Wang (Molecular Biology Reports, 2014)

Effects of submerged macrophytes on the abundance and community composition of ammonia-oxidizing prokaryotes in a eutrophic lake - Da-yong Zhao; Juan Luo; Jin Zeng; Meng Wang; Wen-ming Yan; Rui Huang; Qinglong L. Wu (Environmental Science and Pollution Research, 2014)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Knockdown of ZNF403 inhibits cell proliferation and induces G2/M arrest by modulating cell-cycle mediators - Rui Guan; Xiao-Yan Wen; Jing Wu; Rongqi Duan; Huibi Cao; Simon Lam; Defu Hou; Youdong Wang; Jim Hu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Morphological and photosynthetic variations in the process of spermatia formation from vegetative cells in Porphyra yezoensis Ueda (Bangiales, Rhodophyta) and their responses to desiccation - Rui-Ling Yang; Wei Zhou; Song-Dong Shen; Guang-Ce Wang; Lin-Wen He; Guang-Hua Pan (Planta, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

The Electrostatic Interactions Between Nano-TiO2 and Trypsin Inhibit the Enzyme Activity and Change the Secondary Structure of Trypsin - Wen-Rui Wang; Rong-Rong Zhu; Rong Xiao; Hui Liu; Shi-Long Wang (Biological Trace Element Research, 2011)

Effects of low nitrogen and drought stresses on proline synthesis of Jatropha curcas seedling - Wen-Guo Wang; Rui Li; Bin Liu; Liang Li; Sheng-Hua Wang; Fang Chen (Acta Physiologiae Plantarum, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Multiple induced mutagenesis for improvement of ethanol production by Kluyveromyces marxianus - Zong-wen Pang; Jing-juan Liang; Xiao-juan Qin; Ji-rui Wang; Jia-xun Feng; Ri-bo Huang (Biotechnology Letters, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans - Qiu-Li Wu; Qi Rui; Ke-Wen He; Lu-Lu Shen; Da-Yong Wang (Neuroscience Bulletin, 2010)

Bacterial communities in PAH contaminated soils at an electronic-waste processing center in China - Wen Zhang; Hui Wang; Rui Zhang; Xie-Zhi Yu; Pei-Yuan Qian; M. H. Wong (Ecotoxicology, 2010)

Synthesis, Characterization, DNA-Binding and Antiproliferative Activity of Nd(III) Complexes With N-(Nitrogen Heterocyclic) Norcantharidin Acylamide Acid - Wen-Zhong Zhu; Qiu-Yue Lin; Mei Lu; Rui-Ding Hu; Xiao-Liang Zheng; Jian-Ping Cheng; Yun-Yun Wang (Journal of Fluorescence, 2009)

Nitric oxide increases Wnt-induced secreted protein-1 (WISP-1/CCN4) expression and function in colitis - Hongying Wang; Rui Zhang; Shoubin Wen; Donna-Marie McCafferty; Paul L. Beck; Wallace K. MacNaughton (Journal of Molecular Medicine, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Transgenic Mice Can Express Mutant Human Coagulation Factor IX with Higher Level of Clotting Activity - Jing-Bin Yan; Shu Wang; Wen-Ying Huang; Yan-Ping Xiao; Zhao-Rui Ren; Shu-Zheng Huang; Yi-Tao Zeng (Biochemical Genetics, 2006)

Identification and functional characterization of a leucine-rich repeat receptor-like kinase gene that is involved in regulation of soybean leaf senescence - Xiao-Ping Li; Rui Gan; Peng-Li Li; Yuan-Yuan Ma; Li-Wen Zhang; Ren Zhang; Yong Wang; Ning Ning Wang (Plant Molecular Biology, 2006)

Arabidopsis thaliana UBC13: Implication of Error-free DNA Damage Tolerance and Lys63-linked Polyubiquitylation in Plants - Rui Wen; Lindsay Newton; Genyi Li; Hong Wang; Wei Xiao (Plant Molecular Biology, 2006)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)